2022
DOI: 10.3390/su14169901
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning and Multivariate Statistics to Predict Uniaxial Compressive Strength and Static Young’s Modulus Using Physical Properties under Different Thermal Conditions

Abstract: Keywords: thermal effect prediction model; uniaxial compressive strength; static Young’s modulus; artificial neural network; multilinear regression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 65 publications
0
13
0
1
Order By: Relevance
“…Therefore, the use of artificial intelligence methods can be a good solution to predict FR with a high degree of performance. Additionally, the use of artificial intelligence methods in different fields of mingling and civil engineering indicates the effectiveness of these methods for predicting and optimizing aims [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Of 20mentioning
confidence: 99%
“…Therefore, the use of artificial intelligence methods can be a good solution to predict FR with a high degree of performance. Additionally, the use of artificial intelligence methods in different fields of mingling and civil engineering indicates the effectiveness of these methods for predicting and optimizing aims [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Of 20mentioning
confidence: 99%
“…Also, they found that the density and Schmidt rebound hardness had more related to the UCS than the rock porosity. Khan et al [ 26 ] applied the MLR, ANN, RF, and KNN for predicting the UCS and static E from physical, chemical, and mechanical properties of marble rock namely density, porosity, P-wave velocity, and dynamic E under different thermal conditions. They found that the KNN and RF are reliable approaches to predict both UCS and E. Also, it was found that P-wave velocity has strong correlations with the UCS and E. Based on predictive performance, the RF model was proposed to predict the UCS and E as the best model.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous services and sectors have seen significant productivity gains due to ML. Although it is still in its infancy in the construction sector, its application has grown recently to address several difficulties, including concrete technology 12 16 and concrete durability 17 19 . The other various application in the field of civil and environmental engineering of ML algorithms can be found in the published research work 20 24 .…”
Section: Introductionmentioning
confidence: 99%